Anti‐inflammatory effects of infliximab in mice are independent of tumour necrosis factor α neutralization. (23rd November 2016) - Assas, B. M.; Levison, S. E.; Little, M.; England, H.; Battrick, L.; Bagnall, J.; McLaughlin, J. T.; Paszek, P.; Else, K. J.; Pennock, J. L.
Summary: Infliximab (IFX) has been used repeatedly in mouse preclinical models with associated claims that anti‐inflammatory effects are due to inhibition of mouse tumour necrosis factor (TNF)‐α. However, the mechanism of action in mice remains unclear. In this study, the binding specificity of IFX for mouse TNF‐α was investigated ex vivo using enzyme‐linked immunosorbent assay (ELISA), flow cytometry and Western blot. Infliximab (IFX) did not bind directly to soluble or membrane‐bound mouse TNF‐α nor did it have any effect on TNF‐α‐induced nuclear factor kappa B (NF‐κB) stimulation in mouse fibroblasts. The efficacy of IFX treatment was then investigated in vivo using a TNF‐α‐independent Trichuris muris‐ induced infection model of chronic colitis. Infection provoked severe transmural colonic inflammation by day 35 post‐infection. Colonic pathology, macrophage phenotype and cell death were determined. As predicted from the in‐vitro data, in‐vivo treatment of T. muris‐ infected mice with IFX had no effect on clinical outcome, nor did it affect macrophage cell phenotype or number. IFX enhanced apoptosis of colonic immune cells significantly, likely to be driven by a direct effect of the humanized antibody itself. We have demonstrated that although IFX does not bind directly to TNF‐α, observed anti‐inflammatory effects in other mouse models may be through host cell apoptosis. We suggest that more careful consideration of xenogeneic responses should be made when utilizing IFX in preclinical models. Abstract : Infliximab, a humanised antibody designed to neutralise TNFalpha, has frequently been used in mouse models of inflammation to demonstrate the importance of TNFalpha in disease. In agreement with early publications describing the antibody, here we show categorically that infliximab does not bind mouse TNFalpha, nor does it affect the functionality of murine TNFalpha, although it does cause significant apoptosis at the site of inflammation. These data show that infliximab has little value as a TNFalpha neutralising antibody in mice.